2011
DOI: 10.1111/j.1365-2923.2010.03920.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Important… but of low status’: male education leaders’ views on gender in medicine

Abstract: The results indicate that male faculty leaders embrace the importance of gender-related issues, but do not necessarily recognise or defend their impact on an area of significant knowledge and competence in medicine. To change this and to engage more men in gender education, faculty measures are needed to counteract prejudice and to upgrade the time allocation, merits and status of gender implementation work. Based on our findings, we present and discuss possible ways to interest more men and to improve gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 52 publications
3
58
0
Order By: Relevance
“…The minor impact and level of unawareness of gender differences, from the medical teacher’s perspective, was also found in other studies 1,3,12. A semi-structured interview study conducted with 20 male education leaders from Sweden showed that all informants regarded gender as important, but of low status 12.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The minor impact and level of unawareness of gender differences, from the medical teacher’s perspective, was also found in other studies 1,3,12. A semi-structured interview study conducted with 20 male education leaders from Sweden showed that all informants regarded gender as important, but of low status 12.…”
Section: Discussionsupporting
confidence: 63%
“…Clinical teachers involved in clerkship programs play a key role in drawing attention to gender. Most male faculty leaders understand the importance of gender-related issues, but do not recognize gender as an area of significant knowledge and competence in medicine 12. Female clinical teachers are more likely than men to consider the physician’s gender an important element in consultation, clinical tutoring, and in interactions with colleagues 13…”
Section: Introductionmentioning
confidence: 99%
“…They also have worse perceptions of their academic achievement than male students [56], indicating a more critical self-perception among female students. Moreover, high academic demands in a gender-discriminatory environment during the final years of medical school [57], [58] may result in social isolation and this may explain why scores on perceptions about social relationships are lower among clerkship female students.…”
Section: Discussionmentioning
confidence: 99%
“…To face discrimination was therefore surprising and induced feelings of shame and personal failure, leading the female students to often blame themselves for causing the unfair treatment instead of actively protesting such treatment. A second explanation is related to the strong ideals in medicine about objectivity and neutrality that have been shown to socialize medical students to believe that aspects like gender, as well as class, ethnicity, and sexual orientation, are, or should be, insignificant for their own working conditions [20, 39, 40]. Students’ adaptation to such ideals might explain why some of the female students had their experiences of unfair treatment questioned by their peers.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the importance of gender awareness in medical education has received attention in recent years [1316], and many medical schools have included education about gender in their curricula [1719]. However, such gender education has often been met with scepticism and resistance, and researchers in the field attribute this resistance to attitudes and values among students as well as teachers [16, 20]. This shows that formal curricular content must be viewed in the context of what is sometimes labelled the “hidden curriculum” [21], referring to the fact that many critical determinants of medical education do not operate within the formal curriculum, but through attitudes, values, and behaviours communicated in everyday interactions and clinical encounters.…”
Section: Introductionmentioning
confidence: 99%